Antimicrobial activity and Identification of fungus associated Stylissa flabelliformis sponge collected from Menjangan Island West Bali National Park, Indonesia - Erna Prawita Setyowati; Silvia Utami Tunjung Pratiwi; Purwantiningsih Purwantiningsih; Oka Samara (Indonesian Journal of Pharmacy, 2018)
The Fungus is a very important microorganism as a producer of bioactive secondary metabolites. Active substances of microbial origin have been sought through the process of screening methods to obtain antimicrobial compounds. The purpose of this study was to isolate fungi associated with sponge taken from Menjangan Island National Park West Bali (Indonesia) and identify fungi that have antimicrobial activity. Isolation of fungus from sponge was carried out by spread plate method using Saboroud Saline Agar medium. Each fungi will be tested to Staphylococcus aureus ATCC 29213, Escherichia coli ATCC 25922 and Candida albicans ATCC 10231. Identification of fungi is based on the observation of macroscopic, microscopic and also using 16rRNA/ITS phylogeny tree. The results showed that S. flabelliformis sponge had 10 fungal isolates. Most of them have antimicrobial activity. The name associated with a sponge fungus is These 10 fungus are Aspergillus flavus strain UPMZ02, Aspergillus fumigatus strain CD1621, Trichoderma reesei strain JCM 2267, Aspergillus nomius strain KUB105, Aspergillus sp. strain TLWK-09, Aspergillus flavus strain MC-10-L, Penicillium sp. strain RMA-2, Aspergillus sp. strain TLWK-09, Aspergillus fumigatus and Trichoderma reesei strain TV221